PENGARUH KEMASAN PRODUK, INOVASI PRODUK DAN DISPLAY PRODUK TERHADAP MINAT BELI ULANG DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA PRODUK RENGGINANG CAP TIGA BINTANG DI DESA GELUNG SITUBONDO - Natania, Fela Olivia; Karnadi, Karnadi; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2024)
The growth of a company depends on its ability to design strategies. Because, strategy encourages companies to look forward and actively try to create their future. The aim of this research is to analyze and test the influence of product packaging, product innovation and product display on repurchase interest with purchase decisions as an intervening variable. The population in this research is consumers of Rengginag Cap Tiga Bintang. This sampling technique is simple random sampling. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that product packaging has a significant positive effect on purchasing decisions, product innovation has a significantly positive effect on purchasing decisions, product display has a positive but not significant effect on purchasing decisions, product packaging has a positive but not significant effect on purchasing decisions. Intention to repurchase, Product innovation has a significant positive effect on Intention to repurchase, Price discounts have a positive but not significant effect on Intention to repurchase, Purchase decisions have a positive but not significant effect on Intention to repurchase, Product packaging has a positive but not significant effect on Intention to repurchase through Purchasing decisions not significant, Product innovation on repurchase interest through purchase decisions has a positive but not significant effect, Product display on repurchase interest through purchase decisions has a positive but not significant effect.